Gods, goddesses, and monsters : a book of mythology - Keenan, Shiela (New York : Scholastic Reference, 2000)
Discusses the characters and themes of the myths of peoples from Asia to Africa to North and South America.
Keywords: Mythology -- Juvenile literature; Folklore